Handbook of research on improving learning and motivation through educational games multidisciplinary approaches - Felicia, Patrick (Information Science Reference, 2011)
"This book provides relevant theoretical frameworks and the latest empirical research findings on game-based learning to help readers who want to improve their understanding of the important roles and applications of educational games in terms of teaching strategies, instructional design, educational psychology and game design" - Provided by publisher